2004
DOI: 10.1249/01.mss.0000113684.61351.b0
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Eccentric Loading of the Knee with the Pose Running Method

Abstract: Pose running was associated with shorter stride lengths, smaller vertical oscillations of the sacrum and left heel markers, a neutral ankle joint at initial contact, and lower eccentric work and power absorption at the knee than occurred in either midfoot or heel-toe running. The possibility that such gait differences could be associated with different types and frequencies of running injuries should be evaluated in controlled clinical trails.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 21 publications
5
74
2
4
Order By: Relevance
“…In addition, the greater knee excursion of the RS runners contributed to their having to generate greater KENW and attenuating vertical ground reaction forces through the knee joint instead of through the ankle joint, as did the Chi runners. This finding is consistent with Arendse et al, 1 who reported reduced KENW and greater APNW in a group of Pose runners who used a forefoot-strike pattern compared to runners who used either a midfoot-strike or RS pattern.…”
Section: Kinematic Variablessupporting
confidence: 91%
“…In addition, the greater knee excursion of the RS runners contributed to their having to generate greater KENW and attenuating vertical ground reaction forces through the knee joint instead of through the ankle joint, as did the Chi runners. This finding is consistent with Arendse et al, 1 who reported reduced KENW and greater APNW in a group of Pose runners who used a forefoot-strike pattern compared to runners who used either a midfoot-strike or RS pattern.…”
Section: Kinematic Variablessupporting
confidence: 91%
“…This is important, as barefoot running as well as adopting a forefoot or midfoot strike pattern has been shown to increase the mechanical demand of the ankle plantar flexors. 2,5,8,19,31,35,46 Furthermore, post hoc analysis revealed that there was no significant difference in ankle plantar flexor moment at the time of peak PFJ stress across the 3 trunk conditions. We propose that adopting a forward-lean trunk posture during running may be a preferable strategy to reduce PFJ stress without increasing the mechanical demand on ankle plantar flexors.…”
Section: Discussion Tmentioning
confidence: 93%
“…Peak PFJ stress was significantly lower in the flexed condition (mean  SD, 20.2  3. at the ankle plantar flexors. 2,5,8,19,31,35,46 Recent studies suggest that sagittal plane trunk posture may be associated with tibiofemoral joint biomechanics during weight-bearing activities. For example, a forward trunk lean posture has been found to be associated with lower knee extensor moments during walking, stair ascent, and single-leg-hop landing.…”
Section: T T Resultsmentioning
confidence: 99%
“…2,47 The MSA runners, however, used increased ankle excursion and increased APNW to reduce the vertical ground reaction force loading rate. Arendse et al 13 also observed reduced KENW and greater APNW in a group of Pose runners who used a forefoot-strike pattern compared with runners who used either a midfoot or rear-foot-strike pattern.…”
Section: Work Variablesmentioning
confidence: 89%
“…7,8 Several biomechanical researchers [9][10][11][12] have observed that most runners demonstrate a rear-foot-strike pattern. Rearfoot-strike running, with the heel making initial contact with the ground, has been associated with greater knee-joint loading 13 and greater initial vertical-loading rates than running with a more anterior-foot-strike pattern. 9 Running with an increased stride frequency may reduce knee-joint loading.…”
mentioning
confidence: 99%